Proyecto de inversión para la producción y comercialización de cerraduras eléctricas en la ciudad de Guayaquil. - Figueroa Filián, Janina Estefanía (2010)
The burglaries to homes, businesses and offices are a major concern of our community. ESPOL studies determined that most thefts are done destroying doors, padlocks and locks.